Performance analysis and optimization in turning of ASTM A36 through process capability index - Abhijit Saha; Himadri Majumder (Journal of King Saud University: Engineering Sciences, 2018)
Organizations now a days acquaint process capability index (Cpi) to appraise the quality of their items with an aim to improve quality and cut down the operating costs which enhance the productivity and help them to stay competitive. In this paper process capability study is performed for turning operation, keeping in mind the end goal to check the process performance within specific limits. Three process input like spindle speed, feed and depth of cut has been chosen for process capability study in plain turning operation following Taguchi’s L27 orthogonal array. Process capability index was evaluated for two machining attributes frequency of tool vibration and average surface roughness. Single response optimization was executed for these two machining qualities to explore the input settings, which could optimize turning process ability. Optimum parameter settings for frequency of tool vibration and average surface roughness were found to be spindle speed: 240 rpm, feed: 0.16 mm/rev, depth of cut: 0.2 mm. and spindle speed: 240 rpm, feed: 0.16 mm/rev, depth of cut: 0.1 mm. respectively. Keywords: Frequency of tool vibration, Process capability analysis, Surface roughness, Turning